Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Muslim di Tiktok Shop - Ulfa, Wulan Santika; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2022)
This research examines factors that affect buying decisions of Muslim consumers at Tiktok Shop. The existence of Tiktok Shop as one of the e-commerce sites in Indonesia is quite recent, start at 2020. In 2019, e-commerce growth is growing very rapidly in Indonesia up to 78%. The method in this study is quantitative with the measuring instrument is a Likert scale and the data analysis technique is multiple linier regression analysis. The factors studied are price, convenience, and promotion. The result showed from the T test that the factors had a significant influence partially on the purchasing decisions. And the F test also resulted that the factors studied had a simultaneous influence on purchasing decisions. So it can be concluded that in the process of purchasing decisions at Tiktok Shop, Muslim consumers pay attention to product prices, ease of application, and also promotions carried out.